Characterization, antimicrobial, and antioxidant activities of silver nanoparticles synthesized by uricase from Alcaligenes faecalis GH3. (July 2019) - Badoei-dalfard, Arastoo; Shaban, Mojtaba; Karami, Zahra
Abstract: Enzyme-mediated nanoparticles synthesis has found promising attention by researchers. In this project, a powerful uricase-producing bacterium was screened from poultry soil samples which are generally rich in uric acid. GH3 isolate was identified as Alcaligenes -faecalis . Biosynthesis of AgNPs was done using the cell extract of A. faecalis GH3 treated with an aqueous solution of AgNO3 . SEM results show that AgNPs were spherical in shape and were in size ranging from 32 to 49 nm. Also, the zeta potential of synthesized AgNPs in colloidal solution was −21 mV, which displays the good stability of the particles in the colloidal solution. Results showed that the maximum improvement in antibacterial activity of AgNPs mixed with antibiotic was about 162.5% for ampicillin against B. cereus, compared to antibiotic alone. Furthermore DPPH and ABTS + radical scavenging activities showed increased activities with increasing concentration of AgNPs. IC50 values of AgNPs was obtained as 710 and 220 μg/ml for DPPH and ABTS + scavenging activities, respectively. These results indicate that AgNPs synthesis by cell extract of uricase producing Alcaligenes has potent application in antibacterial and antioxidant approaches. Graphical abstract: Image 1 Highlights: This is the first report on using of the bacterial uricase for AgNPs synthesis. A potent uricase from Alcaligenes faecalis was isolated. Zeta potential of AgNPs in colloidal solution was −21 mV. MIC against S. aureus and B. cereus was calculated as 16 μg/ml. DPPH activity showed that IC50 value of AgNPs was 710 mg/ml.